Structural characteristics of camel-bone gelatin by demineralization and extraction - Al-Kahtani, Hassan Abdullah M.; Jaswir, Irwandi; Ismail, Elsayed Ali; Ahmed, Mohammed Asif; Hammed, Ademola Monsur; Olorunnisola, Saeed; Octavianti, Fitri (Taylor and Francis Inc., 2017)
Camel bone was demineralized through HCl acidulation process at different concentrations (0.0%, 1.5%, 3.0%, and 6.0%) over 1–5 days. The level of demineralization was acid concentration and soaking time dependent. Highest demineralization (62.0%) was recorded in bone sample treated with 6.0% dilute acid for 5 days. Energy dispersive X-ray spectroscopy (EDX) elemental analysis revealed reduction in Ca and increase in N and H, while O remains unaffected. Particulate characteristics by scanning electron microscope showed an increased surface roughness of bone after demineralization. Fourier transform infrared (FT-IR) analysis of ossein depicted the presence of functional group similar to that of bone protein (collagen). Statistical optimization by central composite design (CCD) revealed a significant quadratic model for optimum values of extraction temperature, pH, and extraction time. The highest gelatin yield from camel bone was 23.66% at optimum extraction condition (71.87°C, pH 5.26, and 2.58 h) and the bloom was 205.74 g. Camel bone is suitable for production of gelatin with good potentials in food and nonfood applications. © 2017 Taylor & Francis Group, LLC.